ANALISA KUALITAS PELAYANAN UNTUK MENINGKATKAN KEPUASAN PELANGGAN PADA CV BORNEO JAYA MAJU DI KABUPATEN BARITO KUALA - Sri Mulyani; A. Ghazali (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
The purpose of this research is to find out where the shortcomings are in the services provided in order to increase customer satisfaction at CV Borneo Jaya Maju travel in Barito Regency. The population in this study were customers in May 2021. The sample taken as respondents was 50 customers with a sampling technique using the Arikunto formula. The method used in this study was a quantitative descriptive method. The results of this study are the services provided to customers are still lacking, where the services provided to customers in paying attention to the five dimensions are Physical Evidence (tangible), namely the incompleteness of tourist package advertising brochures and the absence of advertising promos on the website to make it easier for customers to see new information. Responsiveness (responsiveness) of employees in providing understanding solutions about tour packages to customers is still not fully understood by customers and guarantees (assurance) are also still lacking so that there are still some customers who are not satisfied with this.